Seropositivity to SARS-CoV-2 in Alberta, Canada in a post-vaccination period (March 2021–July 2021). Issue 9 (2nd September 2022) - Kanji, Jamil N.; Nguyen, Leonard T.; Plitt, Sabrina S.; Charlton, Carmen L.; Fenton, Jayne; Braun, Sheila; Marohn, Carol; Lau, Cheryl; Svenson, Lawrence W.; Hinshaw, Deena; Lutsiak, Christie; Zelyas, Nathan; et al.
Abstract: Background: The COVID-19 pandemic has necessitated the need to rapidly make public health decisions. We systematically evaluated SARS-CoV-2 seropositivity to understand local COVID-19 epidemiology and support evidence-based public health decision making. Methods: Residual blood samples were collected for SARS-CoV-2 receptor binding domain (RBD) IgG testing over a 1–5 day period monthly from 26 February 2021–9 July 2021 from six clinical laboratories across the province of Alberta, Canada. Monthly crude and adjusted (for age and gender) seropositivity were calculated. Results were linked to provincial administrative, laboratory, and vaccine databases. Results: 60, 632 individual blood samples were tested. Vaccination data were available for 98.8% of samples. Adjusted RBD IgG positivity rose from 11.9% (95% confidence interval [CI] 11.9–12.0%) in March 2021 to 70.2% (95% CI 70.2–70.3%) in July 2021 ( p < .0001). Seropositivity rose from 9.4% (95% CI 9.3–9.4%) in March 2021 to 20.2% (95% CI 20.1–20.2%) in July 2021 in unvaccinated Albertans. Unvaccinated seropositive individuals were from geographic areas with significantly ( p < .001) lower median household income, lower proportion of married/common-law relationships, larger average household size and higher proportions of visible minorities compared to seronegative unvaccinated individuals. In July 2021, the age groups with the lowest and highest seropositivity in unvaccinated Albertans were those ≥80 years (12.0%, 95% CI 5.3–18.6%) and 20–29 years (24.2%, 95% CI 19.6–28.8%), respectively. Of seropositive unvaccinated individuals, 50.2% (95% CI 45.9–54.5%) had no record of prior SARS-CoV-2 molecular testing. Conclusions: Longitudinal surveillance of SARS-CoV-2 seropositivity with data linkage is valuable for decision-making during the pandemic.